Incendiary Kites and Balloons: Anti-Colonial Resistance in Palestine's Great March of Return - Stefanini, Pietro (PARTECIPAZIONE E CONFLITTO, 2021)
This paper examines the Palestinian use of incendiary kites and balloons that emerged during Gaza's Great March of Return. Kites and balloons are rarely thought of as unstoppable weapons in contemporary theatres of war and resistance. Yet, for an extended period the Israeli military was unable to halt these aerial explosives from burning large quantities of agricultural fields and natural forests surrounding the Gaza Strip. The article critiques the security literature that discusses this new method of Palestinian resistance as another instance of terrorism. Instead, by drawing on Palestinian and Fanonian theorisations of violence in anti-colonial movements, I attempt to make the kites and balloons legible as a form of indigenous resistance to settler colonialism that can be an internally mobilising tool for Palestinians. The paper argues that the low-tech aerial explosives were mobilised as a response to high-tech militarism and long-standing settler colonial processes still shaping dynamics on the ground. These innovative forms of resistance momentarily broke the siege imposed on the Gaza Strip and in burning trees planted to cover destroyed Palestinian villages open up questions surrounding the struggle over land in Israel/Palestine. The paper concludes by delineating how despite some immediate breakthroughs, it remains questionable whether these militant kites and balloons are long-term politically viable techniques of resistance.